Attracted to the Hustle? An Impression Management Perspective on Entrepreneurial Hustle in New Venture Recruitment - Bastian Kindermann; Anna Hocker; Steffen Strese (Journal of Management Studies, 2023)
Abstract Research has shown that impression management helps entrepreneurs access critical resources, but insights into applying concrete impression management techniques in new venture recruitment remain scarce. This knowledge gap represents a challenge for new ventures facing disadvantages in recruitment. We propose self-presentations of entrepreneurial hustle as an effective impression management technique for entrepreneurs. Such self-presentations to applicants increase the perceived competence and thereby the attractiveness of entrepreneurs' new ventures. We introduce applicants' individual entrepreneurial orientation and entrepreneurs' gender as factors influencing the relationship between entrepreneurial hustle and perceived entrepreneurial competence. Employing an experimental vignette methodology across three samples – a main sample drawn from mTurk (N0.167em=0.167em613) and two additional samples from Prolific (N0.167em=0.167em130) and German management students (N0.167em=0.167em188) – we find that perceived competence mediates the relationship between entrepreneurial hustle and perceived organizational attractiveness. While individual entrepreneurial orientation weakens the effect of entrepreneurial hustle self-presentations on perceived competence, we do not find an influence of entrepreneurs' gender. This research indicates mechanisms and contingencies regarding the effect of entrepreneurial hustle self-presentations. Our results advance not only research on entrepreneurial hustle but also theory on interviewer-level impression management and new venture recruitment.
Keywords: 330; entrepreneurial behaviours; entrepreneurial hustle; individual entrepreneurial orientation; new venture recruitment; organizational attractiveness